2006
DOI: 10.1126/science.1119311
|View full text |Cite
|
Sign up to set email alerts
|

Role of Noradrenergic Signaling by the Nucleus Tractus Solitarius in Mediating Opiate Reward

Abstract: Norepinephrine (NE) is widely implicated in opiate withdrawal, but much less is known about its role in opiate-induced locomotion and reward. In mice lacking dopamine beta-hydroxylase (DBH), an enzyme critical for NE synthesis, we found that NE was necessary for morphine-induced conditioned place preference (CPP; a measure of reward) and locomotion. These deficits were rescued by systemic NE restoration. Viral restoration of DBH expression in the nucleus tractus solitarius, but not in the locus coeruleus, rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(118 citation statements)
references
References 27 publications
6
112
0
Order By: Relevance
“…CREB is phosphorylated and activated in the amygdala by several drugs of abuse including opiates (Konradi et al, 1994;Olson et al, 2006;Shaw-Lutchman et al, 2002). In addition, opiate withdrawal induced by naloxone can also increase CREB phosphorylation in cultured neurons and in vivo (Chartoff et al, 2003), an effect that is abolished by coadministration of galanin (Hawes et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CREB is phosphorylated and activated in the amygdala by several drugs of abuse including opiates (Konradi et al, 1994;Olson et al, 2006;Shaw-Lutchman et al, 2002). In addition, opiate withdrawal induced by naloxone can also increase CREB phosphorylation in cultured neurons and in vivo (Chartoff et al, 2003), an effect that is abolished by coadministration of galanin (Hawes et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…Galanin also regulates the levels and release of a number of neurotransmitters, including dopamine, acetylcholine, and norepinephrine (Pieribone et al, 1995;Tsuda et al, 1998;Wang et al, 1999). Acute morphine administration increases locomotor activity and results in a conditioned place preference (CPP) (Suzuki et al, 1993;Wise, 1987) and these behaviors can be modulated by dopaminergic agents (Chang et al, 2004;Zarrindast et al, 2006a), noradrenergic depletion, or cholinergic receptor antagonists (Hikida et al, 2003;Olson et al, 2006;Rezayof et al, 2006;Zarrindast et al, 2006b). Thus, galanin may modulate the rewarding and locomotoractivating effects through modulation of multiple neurotransmitter systems.…”
Section: Introductionmentioning
confidence: 99%
“…Because CPP is an associative learning paradigm, manipulations of NE could alter the development or expression of a psychostimulant CPP in the absence of any effect on the rewarding properties of the drugs. However, this is unlikely, as mice that completely lack NE still express a normal conditioned taste aversion to lithium chloride and ethanol and show a CPP to food (Weinshenker et al, 2000;Schank et al, 2006;Olson et al, 2006). Interestingly, NE depletion early in development either has no effect (neonatal 6-OHDA lesion; Spyraki et al, 1982a) or even enhances (DBH knockout mice; Schank et al, 2006) psychostimulant CPP, probably due to compensatory changes in the DA system during development (see below).…”
Section: Ne and Psychostimulant Cppmentioning
confidence: 99%
“…For example, morphine-induced locomotion is abolished in DBH knockout mice that lack NE, a deficit that is partially reversed by pharmacological restoration of NE or viralmediated reexpression of DBH in the DNB or VNB (Olson et al, 2006). In addition, both genetic deletion and pharmacological blockade of a1bARs prevent morphineinduced locomotion (Drouin et al, 2002) and the development of locomotor sensitization (Auclair et al, 2004).…”
Section: Ne and Opiate-induced Locomotion/sensitizationmentioning
confidence: 99%
“…Despite the critical role of DA in the effects of drugs of abuse, some data indicate, however, that noradrenergic rather than dopaminergic transmission is necessary for morphine-induced reward (Drouin et al, 2002b;Hnasko et al, 2005;Ventura et al, 2005;Olson et al, 2006). Whatever the hypothesis, it has been shown that addictive drugs share the ability to induce long-lasting cellular adaptations in neural systems, such as alterations in gene expression (Hyman and Malenka, 2001;Nestler, 2001).…”
Section: Introductionmentioning
confidence: 99%